2011
DOI: 10.1071/mf10314
|View full text |Cite
|
Sign up to set email alerts
|

Plastic and unpredictable responses of stream invertebrates to leaf pack patches across sandy-bottomed streams

Abstract: Detrital inputs to ecosystems provide potential food sources and can produce trophic cascades, but this effect is influenced by whether species specialise in consuming or inhabiting accumulations of detritus. To test whether species are differentially associated with leaves or sand, we compared densities of stream invertebrate species in patches of leaves and bare sand in two sandy-bed creeks in south-eastern Australia, in summer and spring. We also assessed the quality of information on diet and substrate ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Shredders and scrapers were abundant principally in the final periods of decomposition, as a result of the increased palatability of the detritus because of the nutritional value added from microbial and periphyton colonisation (Gessner et al 1999;Gonçalves et al 2006;Yule et al 2009). These facts concord with the observations by Downes et al (2011) and Dudgeon and Wu (1999) in tropical streams, that most species are not specialised for living in leaves, because of the diversity of resources and the low quality of detritus. Our data also indicated that shredders and scrapers are more abundant in artificial leaves, reflecting their generalist behaviour.…”
Section: Functional Feeding Groupssupporting
confidence: 89%
See 1 more Smart Citation
“…Shredders and scrapers were abundant principally in the final periods of decomposition, as a result of the increased palatability of the detritus because of the nutritional value added from microbial and periphyton colonisation (Gessner et al 1999;Gonçalves et al 2006;Yule et al 2009). These facts concord with the observations by Downes et al (2011) and Dudgeon and Wu (1999) in tropical streams, that most species are not specialised for living in leaves, because of the diversity of resources and the low quality of detritus. Our data also indicated that shredders and scrapers are more abundant in artificial leaves, reflecting their generalist behaviour.…”
Section: Functional Feeding Groupssupporting
confidence: 89%
“…In contrast, Godoy and Coutinho (2002) pointed out that the chemical composition of leaves is presumably not the key factor affecting changes in invertebrate colonisation on different types of detritus. In our opinion, this question needs to be studied further, using other plant species, mainly tropical species that are rich in different compounds (Dudgeon and Wu 1999;Moretti et al 2007;Downes et al 2011).…”
Section: Invertebrate Colonisation: Size and Shape Of The Detritusmentioning
confidence: 98%
“…Yearly average rainfall is 800–1000 mL, which falls mostly in winter and spring (Australian Bureau of Meteorology). Discharge varies substantially over the year with average monthly maxima of 1000–1500 ML day −1 during winter to spring, which contrasts with summer flows of <100 ML day −1 on average; however, summer storms may occasionally generate high, bed‐moving flows (Downes et al ., ). Our study was conducted at the end of a drought in the region, dubbed the ‘big dry’ (Ummenhofer et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Instead, many streams have soft sediments such as sand; this includes our study system, Hughes Creek. A prior observational study in Hughes Creek found hydropsychid and ecnomid egg masses in large numbers on bark and, to a lesser extent wood, the availability of which varies widely according to season and flooding as well the presence of donor trees, many of which have been cleared from extensive stretches of the creek (Downes et al ., ). Furthermore, the quantity of bark and egg masses covaried, suggesting that availability of substrata might limit the input of eggs in Hughes Creek (A. Macqueen, unpubl.…”
Section: Introductionmentioning
confidence: 97%
“…Consumers move actively among leaf packs by drift and other movements, and they can subsequently colonize other leaf packs depending on local physical and biological conditions (Minshall and Petersen 1985;Rowe and Richardson 2001;Downes et al 2011). Experimental manipulations of litter quantity in stream channels have demonstrated that consumers can track litter resource patches, resulting in aggregation of individuals and acceleration of leaf decomposition (Richardson 1991;Rowe and Richardson 2001;Tiegs et al 2008).…”
Section: Introductionmentioning
confidence: 97%